Культурные смыслы летних и осенних календарных праздников французов Крыма - Брыжак, О.В. (Культура народов Причерноморья, 2014)
В статье раскрывается диалогический и онтологический смыслы календарного праздника на примере летних и осенних праздников крымских французов. Обосновывается тезис о том, что будучи одновременно самобытными и включенными в природные циклы, в карнавальные действа и повседневный труд, эти праздники помогают постичь уникальность этноса и, вместе с тем, усмотреть в них универсальные культурные смыслы, связанные с традицией, ритуалом, мифологемой У статті розкривається діалогічний і онтологічний смисли календарного свята на прикладі літніх і осінніх свят кримських французів. Обґрунтовується теза про те, що будучи одночасно самобутніми і включеними в природні цикли, в карнавальні дійства і повсякденну працю, ці свята допомагають осягнути унікальність етносу і, разом з тим, угледіти в них універсальні культурні смисли, пов'язані з традицією, ритуалом, мифологемою The article reveals the dialogic and ontological meaning of the calendar holiday, for example, summer and autumn holidays of the Crimean Frenchmen. Specificity "productive" as wine festivals French people was thus added to the festival's grain harvest grape harvest. This indicates a constant presence in the celebration of fragments from the real life of the people, for the people of meaningful elements. Thus, the influence of Catholicism on the calendar holidays proved to be more powerful than orthodoxy: in almost all stages of the abundant feast is celebrated quite strict prohibitions, with the exception of the harvest itself - the hard work and the results were not subject to artificial framework, in connection with which the tradition of carnival festivities most vividly reflected at a stage of harvest festival. In general, calendar holidays of Crimean Frenchmen are considered as those that fully realize the potential of a dialogical calendar holidays of particular ontology in such varieties as harvest festivals, including specific crops - such as grapes. It is grounded that being both distinctive and included in the natural cycles in the carnival and daily work, these festivals help to understand the uniqueness of the nation and, at the same time, to see in them the universal cultural meanings associated with tradition, ritual, myth